Dekada '70 - Rono, Chito S.; Star Cinema Productions ([Metro Manila] Star Cinema, 2002)
Dekada '70 is the story of a middle class family caught in the midst of martial law in the Philippines.
Disc 1 (1 hr., 14 min.) -- disc 2 (58 min.)
VCD.
Producer, Tess V. Fuentes ; story and screenplay, Lualhati Bautista based on her novel Dekada '70.
Vilma Santos, Christopher de Leon, Piolo Pascual.
Keywords: Martial law -- Philippines -- Drama; Feature films -- Philippines